The Rule of Distinct Services of Transport Companies in Customers Satisfaction: A Case Study from Royal Jordanian Airlines - Areiqat, Ahmad Yousef; Al-Doori, Jamal Ahmed; Alsaleem, Abdulsada Mutlaq; Ahmad, May Mousa (ExcelingTech, 2019)
This study aims to explore the extent of offering distinctive services by the Royal Jordanian Airlines transport company to the travelers on its aircraft. The study relied on data collected from the company's profile and website. And through the benchmarking between the services of Royal Jordanian Airlines with some international airlines companies, and the services standardized by the International Air Transport Association, the results showed: Royal Jordanian Airline Provides pre-flight services such as; possibility to book by phone or internet with the lowest fare, notify travelers of known delays if any, deliver baggage on time, refund of the ticket to the client in case of his apology for travel. Royal Jordanian pays more attention to the passengers with disabilities and special needs in terms of providing those comfortable seats and equipment that help them to move, in addition to kind treatment and special food. As one of the in-flight services, Royal Jordanian Airlines accepts unaccompanied minors ages 5-14 years with 100 as an escort service charge per direction. Royal Jordanian Airlines is seeking to improve the quality of food and beverages offered to passengers in terms of taking into account the conditions of diabetes and pressure. Services provided to mitigate passenger inconvenience from cancellations and misconnections are from the post-flight services.